2020
DOI: 10.7150/jca.39651
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-derived SPARC Attenuates M2-mediated Pro-tumour Phenotypes

Abstract: Since the theory of seed and soil was put forward, people have increasingly recognized that the tumour microenvironment is an important regulator of tumour progression and therapeutic response. Among them, M2-type macrophages (M2, as the major macrophage subtype in the tumour foci) have important promoting effects on various biological behaviours. Secreted protein acidic and rich in cysteine (SPARC) is an important anti-tumour component in the microenvironment of gastric cancer. This study shows that macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…However, Hu et al showed that SPARC upregulation in M2-type macrophages can inhibit M2-mediated promotion of growth, migration and antiapoptotic effects in gastric cancer (GC). SPARC is a key tumor suppressor in GC, which demonstrates the high specificity of SPARC in different cancers [32]. Here, we showed that the expression of SPARC was increased in M2-polarized macrophages and TAMs, which is similar to the results of Johannes et al…”
Section: Discussionsupporting
confidence: 91%
“…However, Hu et al showed that SPARC upregulation in M2-type macrophages can inhibit M2-mediated promotion of growth, migration and antiapoptotic effects in gastric cancer (GC). SPARC is a key tumor suppressor in GC, which demonstrates the high specificity of SPARC in different cancers [32]. Here, we showed that the expression of SPARC was increased in M2-polarized macrophages and TAMs, which is similar to the results of Johannes et al…”
Section: Discussionsupporting
confidence: 91%
“…Also, SPARC-/- mice were shown to mount insufficient innate immune responses [ 130 ]. In addition to tumor cells and fibroblasts, M2 macrophages have been shown to be a major source of SPARC in gastric cancer [ 131 ]. Moreover, this recent study demonstrated that SPARC overexpression in M2 macrophages reduced M2-mediated functions including proliferation of gastric cancer cells, emphasizing the anti-tumorigenic role of SPARC in digestive cancers [ 131 ].…”
Section: Immune Regulation By Ecm Proteins In Digestive Cancersmentioning
confidence: 99%
“…Similarly, the expression of the infected-specific top likelihood genes Cxcl2 , Cd36, and Pdpn was associated with the presence of efferocytic M2-like macrophages ( Figure S5F , green clusters). The distant Sparchi macrophage cluster 5 exhibited C-C chemokine receptor type 7 ( Ccr7 ) exhaustion ( Figure S5F , red clusters), indicating that these cells might be of M1-like origin (Hu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%